2020
DOI: 10.3389/fonc.2020.00216
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxygenkwanin Inhibits Class I HDAC Expression and Synergistically Enhances the Antitumor Activity of Sorafenib in Liver Cancer Cells

Abstract: Abnormal histone deacetylase (HDAC) expression is closely related to cancer development and progression. Many HDAC inhibitors have been widely used in cancer treatment; however, severe side effects often limit their clinical application. In this study, we attempted to identify natural compounds with HDAC inhibitory activity and low physiological toxicity and explored their feasibility and mechanisms of action in liver cancer treatment. A yeast screening system was used to identify natural compounds with HDAC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 71 publications
(70 reference statements)
0
17
0
1
Order By: Relevance
“…Qualitative and quantitative UPLC-ESI-MS/MS analyses show that 352 metabolites including 11 terpenoids, 35 alkaloids, 80 phenolic acids, 25 coumarins, 7 lignans, 184 flavonoids and 10 other compounds were detected and identified, among which 15 metabolites are unique to DHP and 16 metabolites are unique to BZH. Among these unique compounds, phlorizin was studied as a potential pharmaceutical treatment for type 2 diabetes [33]; Hydroxygenkwanin has antitussive, expectorant and antiasthmatic effects [34]; Cosmosiin has anti-tumor, antiinflammatory and anti-virus effects [35]; Avicularin has antihypertensive, antitussive and expectorant effects [36]. Those active ingredients could all be used as potential biomarkers for identifying the two cultivars.…”
Section: Plos Onementioning
confidence: 99%
“…Qualitative and quantitative UPLC-ESI-MS/MS analyses show that 352 metabolites including 11 terpenoids, 35 alkaloids, 80 phenolic acids, 25 coumarins, 7 lignans, 184 flavonoids and 10 other compounds were detected and identified, among which 15 metabolites are unique to DHP and 16 metabolites are unique to BZH. Among these unique compounds, phlorizin was studied as a potential pharmaceutical treatment for type 2 diabetes [33]; Hydroxygenkwanin has antitussive, expectorant and antiasthmatic effects [34]; Cosmosiin has anti-tumor, antiinflammatory and anti-virus effects [35]; Avicularin has antihypertensive, antitussive and expectorant effects [36]. Those active ingredients could all be used as potential biomarkers for identifying the two cultivars.…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, previous studies suggest that the p53 protein can regulate the expression of RAD51 by binding to the p53 response element on the RAD51 promoter and inhibiting the transcription of the RAD51 gene [ 55 ]. Our previous study has shown that HGK can improve the binding ability of p53 to the target gene promoter by stimulating the acetylation of p53 [ 46 ]. Therefore, we hypothesized that the acetylation of p53 due to HGK can promote the binding of p53 to the RAD51 promoter, thereby negatively regulating the expression of RAD51.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxygenkwanin (HGK) is a flavonoid extracted from Daphne genkwa , which not only has anti-inflammatory properties, but also induces mitochondrial damage and DNA breaks in glioma cells, leading to cell cycle arrest and apoptosis [ 44 , 45 ]. In addition, our previous research has shown that by inhibiting the expression of the transcription factor, FOXM1, and Class I histone deacetylase (HDAC), HGK can inhibit the growth, migration, and invasion of liver cancer cells, thereby promoting cellular apoptosis [ 46 , 47 ]. In this study, we aimed to identify a natural compound that could inhibit DDR, using a single-strand annealing (SSA) yeast-cell analysis system.…”
Section: Introductionmentioning
confidence: 99%
“…Viability was assayed by staining with trypan blue and/or MTT, as described previously [ 19 ]. Combination index (CI) values were calculated to define the synergistic or additive effects of treatment as previously described [ 20 ].…”
Section: Methodsmentioning
confidence: 99%